Aggression among Slovak males training in martial arts versus other sports disciplines - Gorner, K.; Makarowski, R.; Roskova, M. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2021)
Background. Research shows that sports training allows for reducing aggressive behaviors. However, the influence of certain sports disciplines can also intensify them. Results of studies on the influence of sports on aggression levels are inconclusive. Well-founded psychological theories are relatively rarely used to explain these differences.Materials and methods. 480 men training in hockey, basketball, volleyball, martial arts, individual sports, and soccer (junior league, 5th - 4th league, major league) participated in the study. The control group comprised 83 men not participating in any sport. The study was carried out in Slovakia, using Buss and Durkee`s Aggression Questionnaire.Results. Four hypotheses concerning the relationship between aggression levels and duration of training, age, and skill level were tested.Conclusions. 1. In the group of men training in martial arts, the correlations between the duration of training and aggression-re-lated variables, such as assault, irritability, negativism, suspicion, and verbal aggression were negative and of medium strength. 2. Training in martial arts lowers aggression levels. 3. In the group of men training in basketball, a negative correlation between the duration of training and negativism was noted, which means that basketball players do not violate the law or social conventions. 4. In the group of men training in individual sports, a positive correlation between the duration of training and guilt was found. 5. In the group of junior league soccer players, the Pearson`s correlation coefficient for the variable of assault was negative, while it was positive in the 5th - 4th league group, and statistically insignificant in the major league group. 6. The hypothesis stating that sports training lowers aggression levels was not confirmed. It is true only for select sports disciplines.